Cell cycle-dependent phosphorylation of mammalian protein phosphatase 1 by cdc2 kinase - Kwon, Young-Guen (The National Academy of Sciences of the USA, 1997)
Protein phosphatase 1 (PP-1) is known to be a critical component of eukaryotic cell cycle progression. In vitro, our previous studies showed that cdc2 kinase phosphorylates Thr-320 (T320) in PP-1, and that this leads to inhibition of enzyme activity. To examine directly the phosphorylation of PP-1 in intact mammalian cells, an antibody has been prepared that specifically recognizes PP-1Cα phosphorylated at T320. Cell synchronization studies revealed in a variety of cell types that T320 of PP-1 was phosphorylated to high levels only during early to mid-mitosis. The phosphorylation of T320 of PP-1 was reduced by the cyclin-dependent protein kinase inhibitor, olomoucine, and increased by the PP-1/PP-2A inhibitor, calyculin A. Immunofluorescence microscopy using phospho-T320 antibody indicated that in NIH 3T3 cells the phosphorylation of PP-1 began to increase from basal levels in prophase and to peak at metaphase. Immunostaining indicated that phospho-PP-1 was localized exclusively to nonchromosomal regions. Furthermore, in cell fractionation studies of mitotic cells, phospho-PP-1 was detectable only in the soluble fraction. These observations suggest that phosphorylation by cdc2 kinase in early to mid-mitosis and inhibition of PP-1 activity is likely to contribute to the increased state of phosphorylation of proteins that is critical to the initiation of normal cell division.